TonEBP and SMIT expression in human placenta - Shin, Jung-A (Korean Association of Anatomists, 2012)
Tonicity-responsive enhancer binding protein (TonEBP) is a signal transcription factor of transporters such as sodium-myo-inositol cotransporter (SMIT), aldose reductase. TonEBP has a variety of functions such as control of intracellular osmolytes and immunomodulating. It is known that TonEBP is abundant in the placenta, but location and function aren't known. The aim of this study is to describe the localization of TonEBP in the placenta. We assayed the immunohistochemistry of TonEBP and performed in situ hybridization of SMIT in normal human full term placenta. In normal human full term placenta, TonEBP was in villous trophoblasts, extravillous trophoblasts and some endothelial cells. The result of the in situ hybridization of SMIT was similar to that of immunohistochemistry of TonEBP. Neither TonEBP nor SMIT was present in TonEBP knockout mouse placenta. This shows TonEBP is a key factor in SMIT transcription. TonEBP may play an important role in transporting of inositol to fetus in placenta.